Correlation of N-glycan dynamics and interaction network with allosteric antigen binding and Fc receptor recognition - Buyong Ma (Open Exploration Publishing Inc., 2021)
Aim: Fragment crystallizable (Fc) glycans modulate Fc conformations and functions, and glycan may also regulate antigen recognition. In the antibody drug development, glycosylation patterns affect antibody drug characteristics and quality control. In order to provide a global feature of N-glycan interactions in response to antigen and Fc receptor bindings, the interactions among Fc N-glycans and N-glycans’ interaction with Fc CH2 and CH3 domains have been studied. Methods: Molecular dynamics simulations were used to generate conformation ensembles of free antibody, antibody-antigen complex, antibody-human Fc-gamma-receptor-I (hFcγRI) and antibody-antigen-hFcγRI, the hydrogen bonds and radial distance distribution involving N-glycans carbohydrate chains have been analyzed. Results: Two important interaction patterns have been observed. The first is the strong but non-specific interactions between two carbohydrate chains in free antibody. Secondly, it has been found that N-glycans carbohydrate chains can directly interact with CH3 domain in free antibody, and that the distance distribution between carbohydrate chains and CH3 domain clearly differentiate the free antibody, antibody-antigen complex, antibody-hFcγRI complex, and final antibody-antigen-hFcγRI complex. Conclusions: N-glycans partially acts as allosteric sensor and respond to antigen and hFcγRI binding.